A new species of Acarnus Gray, 1867 (Porifera, Demospongiae, Acarnidae) from NE Brazil - Nascimento, Elielton; Pinheiro, Ulisses (Zootaxa, 2023)
The synapomorphic character of the genus Acarnus Gray, 1867 is the presence of the cladotylote spicule. Acarnus has 27 valid species worldwide, including five species reported from the Brazilian coast: A. innominatus Gray, 1867, A. nicoleae van Soest, Hooper & Hiemstra, 1991, A. souriei (Lévi, 1952), A. radovani (Boury-Esnault, 1973) and A. toxeata Boury-Esnault, 1973. Here we will describe A. microxeatus sp. nov., whose diagnosis is the presence of smooth microxeas and acanthoxeas, new characters for the genus. We also provide a complete characterization of the skeletal architecture and spicule morphology of A. toxeata, with scanning electron microscopy image (SEM) of the spicule set.